PENGGUNAAN STRATEGI PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN DALAM MENINGKATKAN HASIL BELAJAR SISWA SMA - Yuniarti, Yuniarti; Utomo, Bambang Budi; Okiana, Okiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the use of an â€œActive, Innovative, Creative, Effective, and Funâ€ (PAIKEM) learning strategy to improve improving studentsâ€™ learning outcomes in class X SMAN 2 Sungai Raya. This is an observational study in the form of qualitative research, of which the analysis was presented descriptively. Research data wereÂ collected from Civic Education teacher and tenth-grade IPS 1 students using direct communication, observation, and documentary study techniques. The data collection instruments were interview guidelines, observation sheets, and documentation worksheets. The findings showed that active students included those who actively asked questions, asked for and expressed opinions. Innovative students were those who can deepen their understanding of the material studied not only depend on textbooks but also use technology. Creative students were those who have many ways to understand the material, then are facilitated byÂ the teacher. Effective student was the goal fulfilled after students received the knowledge that was designed at the beginning of learning. Fun learning wasÂ seen from the conducive classroom environment and the friendly, enthusiastic, and cheerful teacher. Based on the finding, there was an increase in studentsâ€™ learning outcomes after implementing PAIKEM learning strategy with the average scores increased from 6,7 to 8,1.Â Â Keywords: PAIKEM, Learning Strategy, Learning Outcomes.